Physical Literacy Mentoring Based On Traditional Sports Activities For Students - Kusnandar; Budi, Didik Rilastiyo; Nurcahyo, Panuwun Joko; Syafei, Muhamad; Kuntarto; Febriani, Ayu Rizky; Widyaningsih, Rindha (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2025)
The problems that occur at the Darul Abror Islamic Boarding School in Purwokerto are low physical literacy and the tendency of students to ignore physical activity. The solution offered in community service activities is to provide physical literacy assistance based on traditional sports activities. The methods used in this PKM activity consist of Community Education and Mentoring. In the community education method, it is carried out by providing education, lectures, interactive discussions, and questions and answers. The mentoring method is carried out by preparing a physical literacy program while implementing it in the form of a traditional sports activities festival. PKM activities were carried out in 8 (eight) meeting sessions starting from the preliminary, implementation, evaluation and follow-up stages. The results of Community Service activities based on the physical activity questionnaire show that the majority of students at the Darul Abror Islamic Boarding School rarely do sports activities. There are 2% of students who do sports activities 3-4 times a week, while the other 10% of students do light sports activities 1-2 times a week. The remaining 88% have never done any sports activities at all. Traditional sports practices are carried out by students by carrying out traditional sports competitions consisting of sack races and beam relay races. Santri participate in traditional sports activities with enthusiasm. It is hoped that with this activity, students can develop healthy living habits and be active in sports.